Pedagogi Hybrid Learning untuk Memperkuat Literasi Digital Guru Madrasah dalam Mencapai SDG 4 (Pendidikan Berkualitas) - Hilyah Ashoumi; Nur Ahid; Diani Fatmawati (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
The Society 5.0 agenda has accelerated the demand for digitally competent teachers, including in Indonesian madrasahs where professional development must also safeguard Islamic educational values. This study develops a conceptual model for transforming madrasah teachers’ digital literacy through hybrid learning and positions the model as a practical contribution to SDG 4 (Quality Education), particularly target 4.c on qualified teachers. Using a systematic literature review and qualitative content analysis, the study synthesizes research on digital literacy, teacher professional development, and hybrid learning in Islamic and general education settings. The findings indicate that effective transformation requires (1) staged capacity building (basic digital skills to advanced media design), (2) pedagogical integration (TPACK-aligned lesson planning for synchronous and asynchronous modes), (3) institutional support (leadership, infrastructure, and policy), and (4) continuous mentoring and evaluation. The proposed model emphasizes iterative training, classroom implementation, reflective coaching, and community-of-practice support to reduce technology resistance and improve instructional quality. This conceptual contribution offers guidance for madrasah leaders and policymakers to design scalable hybrid professional development programs that strengthen teachers’ digital literacy while enhancing equitable access to meaningful learning.